Surface Water assessment in Helmand River Basin - Safi, Abdul Ghias; Reshteen, Sediqullah (Journal of Natural Sciences – Kabul University, 2023)
In the past few decades, the water resources in various areas of the Helmand River Basin have been affected and as well as it is drying up in some areas as the reason of rapid population growth, inappropriate water harvesting & management, environmental problems, climate changes, air pollution, wars, migrations and so on. In this article, the assessment of water in the Helmand River Basin has been briefly reviewed. Several years of data related to climatic changes, especially water flow and precipitation have been collected and subjected to comprehensive research and evaluation. At the end of the article, the problems and affects in the Helmand River Basin have been analyzed and appropriate solutions have been suggested.